Sequential severe immune-related adverse events induced by PD-1 inhibitor: a case report and literature review - Xia, Jinxiong; Wen, Yingmei; Xiao, Mengxia; Ye, Dafu; Gao, Yanjun; Tang, Dongling; Zhang, Xiuyun; Chen, Jinling; Li, Qingqing; Yao, Yi (Frontiers in Oncology, 2024)
In a variety of cancers, immune checkpoint inhibitors (ICIs) have demonstrated substantial survival advantages. Nevertheless, the widespread use of ICIs in the clinic has resulted in a growing interest in immune-related adverse events (irAEs) and their treatment methods. This paper reports a case in which a patient with three sequential severe irAEs was successfully treated. After undergoing two regimens of sintilimab in conjunction with chemotherapy for advanced lung cancer, the patient developed myocarditis combined with hepatitis. Subsequently, the patient developed pneumonia following remission from treatment. We also discuss the mechanism of irAEs, principles of treatment, and progress in the study of biomarkers for early prediction of irAEs by reviewing the literature.